2018
DOI: 10.15761/ifnm.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil replacement in mayonnaise by chia (Salvia hispanica L) mucilage

Abstract: Chia mucilage, composed mainly of dietary fibers, is obtained by immersing chia seeds in water, where the formation of a mucilaginous transparent gel occurs due to the presence of hydrophilic molecules that combine with water. This gel has many properties, among them the emulsifier. Mayonnaise is one of the most consumed condiments, however it contains 70 to 80% of oil. In addition, currently, it exists a growing demand for healthier foods with reduced fat. The objective of this work was to verify the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The 24 h sample had a low cohesiveness value (-61.42 ± 2.11 g) thus indicating a low stickiness. In another study, mayonnaise prepared by using chia seeds as alternative emulsifier showed good physical properties where firmness, consistency, and cohesiveness were 127.53 ± 7.40 g, 4538.57 ± 214.82 g/s and -131.56 ± 7.64 g, respectively (Fernandesa and Mellado, 2018). Moreover, the mayonnaise modified with chia seeds showed solid properties due Soaking time (h) Brix Viscosity (mPas) Peptides (mg/mL) 12 5.09 ± 0.00 b 5.13 ± 0.12 b 0.208 ± 0.103 c 18 5.22 ± 0.00 b 5.73 ± 0.06 b 0.369 ± 0.038 b 24 5.89 ± 0.00 a 7.23 ± 0.06 a 0.463 ± 0.001 a 1 Table 2.…”
Section: Mayonnaise Physiochemical Propertiesmentioning
confidence: 96%
“…The 24 h sample had a low cohesiveness value (-61.42 ± 2.11 g) thus indicating a low stickiness. In another study, mayonnaise prepared by using chia seeds as alternative emulsifier showed good physical properties where firmness, consistency, and cohesiveness were 127.53 ± 7.40 g, 4538.57 ± 214.82 g/s and -131.56 ± 7.64 g, respectively (Fernandesa and Mellado, 2018). Moreover, the mayonnaise modified with chia seeds showed solid properties due Soaking time (h) Brix Viscosity (mPas) Peptides (mg/mL) 12 5.09 ± 0.00 b 5.13 ± 0.12 b 0.208 ± 0.103 c 18 5.22 ± 0.00 b 5.73 ± 0.06 b 0.369 ± 0.038 b 24 5.89 ± 0.00 a 7.23 ± 0.06 a 0.463 ± 0.001 a 1 Table 2.…”
Section: Mayonnaise Physiochemical Propertiesmentioning
confidence: 96%
“…Color is one of the most important quality characteristics of mayonnaise and the first criterion by which consumers decide whether to reject or accept the product (Fernandesa and Salas-Mellado, 2018). As shown in Table 2, the L* value of all mayonnaise formulations in which DEs replaced corn oil was significantly different (P < 0.05) from the control mayonnaise.…”
Section: Color Change Of Mayonnaisementioning
confidence: 99%
“…carbohydrate/protein-based materials have already been used to reduce fat content in mayonnaise, e.g., starch, gum, gelatin, chia mucilage, whey protein, etc. (Mun et al, 2009;Fernandesa and Salas-Mellado, 2018;Yang et al, 2022). However, this study uses a novel approach to reduce oil content in mayonnaise by using an encapsulated phenolic-rich extract of pomegranate peel.…”
Section: Severalmentioning
confidence: 99%
“…The texture properties of the samples, including firmness, consistency, and cohesiveness, were investigated utilizing a texture analyzer model TA-XT2 (Stable Micro Systems, United Kingdom) operated at a temperature of 25°C, following back extrusion procedure outlined by Fernandesa and de las Mercedes Salas Mellado [19] . One hundred twenty mL of samples were delicately placed into cylindrical containers with a volume of 150 mL, possessing a dimension of 80 mm in height and 60 mm in internal diameter.…”
Section: Texture Analysismentioning
confidence: 99%